2019
DOI: 10.5194/tc-13-3383-2019
|View full text |Cite
|
Sign up to set email alerts
|

Multi-tracer study of gas trapping in an East Antarctic ice core

Abstract: Abstract. We study a firn and ice core drilled at the new “Lock-In” site in East Antarctica, located 136 km away from Concordia station towards Dumont d'Urville. High-resolution chemical and physical measurements were performed on the core, with a particular focus on the trapping zone of the firn where air bubbles are formed. We measured the air content in the ice, closed and open porous volumes in the firn, firn density, firn liquid conductivity, major ion concentrations, and methane concentrations in the ice… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 65 publications
(169 reference statements)
1
48
0
Order By: Relevance
“…The high-resolution Modern Dome C, Holocene Dome C, DO6-9 Dome C, and DO21 Vostok methane datasets are available on the World Data Center for Paleoclimatology: https://www.ncdc.noaa.gov/paleo-search/study/28831 (last access: 2 March 2020). The high-resolution Modern Lock-In dataset is available on the PANGAEA database: https://doi.org/10.1594/PANGAEA.909627 (Fourteau et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…The high-resolution Modern Dome C, Holocene Dome C, DO6-9 Dome C, and DO21 Vostok methane datasets are available on the World Data Center for Paleoclimatology: https://www.ncdc.noaa.gov/paleo-search/study/28831 (last access: 2 March 2020). The high-resolution Modern Lock-In dataset is available on the PANGAEA database: https://doi.org/10.1594/PANGAEA.909627 (Fourteau et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…Within the pore closure zone (t ≤ 500 years), the compression speed with increasing pressure is reduced on average by 10%. The discrepancy between modeled and measured air content values in ice cores reported by Fourteau et al (2019) cannot therefore be explained solely by the reduced compressibility of closed pores.…”
Section: Effect Of Internal Pressure On Pore Compressionmentioning
confidence: 78%
“…In real firn, the increased pressure in the already closed bubbles might slow their compression compared to open pores. A recent study by Fourteau et al (2019) has shown that reducing the compressibility of closed pores by an amount of 50% in gas trapping models could explain a discrepancy between model results and direct measurements of air content in ice cores. It is however not clear if this reduced compressibility of 50% is physically sound or not.…”
Section: Effect Of Internal Pressure On Pore Compressionmentioning
confidence: 99%
See 2 more Smart Citations